Group Buying Portals as a Tool for Promoting City Break Holidays - Szymkowiak , Andrzej (Studia Oeconomica Posnaniensia, 2014)
In the initial part of this paper the author identifies the term city break and the factors influencing the decision-making process with regard to the willingness to spend time in such a way as well as choosing the place to spend a city break. The article discusses the issue of the proportion of offers promoting this form of tourism on group buying portals in the total number of offers and in the number of other tourist offers. A quantitative and qualitative analysis has been performed on the offers of group buying portals and on their impact on city breaks. The data, collected between January 2012 and October 2013, made it possible to analyse the deals offered on group buying portals, divided into domestic and foreign as well as long and short breaks. The paper also examines the possibility of using group buying sites targeted at business customers, as well as containing suggestions relating to intensifying efforts to improve the promotion and effectiveness of city tourism, and recommendations for further research.